XANTHOGRANULOMATOUS APPENDICITIS-A RARE HISTOLOGICAL VARIANT - MITTAL, MOHIT; HIREMATH, RAVISHEKAR N; GAUR, NIMISH; VERMA, VISHAL; GHODKE, SANDHYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Xanthogranulomatous inflammation (XGI) is a chronic inflammatory process most commonly described in the case of gall bladder and kidney. The same occurring in the case of the vermiform appendix is a rare occurrence. Here, we describe two cases of appendicitis in which postoperatively histopathological examination revealed typical features of XGI in the appendix.